Determining leadership potential : powerful insights to winning at the talent game - Janson, Kimberly; Rawlings, Melody (Tantor Media, Inc., 2022)
We are in the midst of a leadership crisis that is derailing business success, and it's time to get rigorous about talent. This book will show you how, with an effective and consistent framework to help galvanize decision-makers around leadership potential. Time and time again, organizations place too many leaders in roles that are not a fit. The financial, strategic, and human costs of poor leadership are staggering and unnecessary. But organizations that effectively identify high-potential talent are likely to financially outperform those that do not do this work by a factor of 4.2 to 1, not to mention all the other positive impacts. Backed by the authors' research, including a study with over fifty global CEOs, the insights and strategies packed into this book will help you eliminate the shocking variation that exists in how people think about determining leadership potential-and empower decision-makers to be game-changers to optimize their organizations. For too long, leadership potential has been treated as an imprecise art and inconsistently applied. CEOs, board members, senior managers, and HR professionals will welcome the thought-provoking insights and practical tools this book gives to build a pipeline of strong leaders.